2007
DOI: 10.1196/annals.1415.032
|View full text |Cite
|
Sign up to set email alerts
|

IRX‐2 and Thymosin α1 (Zadaxin) Increase T Lymphocytes in T Lymphocytopenic Mice and Humans

Abstract: Mouse studies showed a synergy of thymosin alpha1 (Talpha1) and a natural cytokine mixture (IRX-2) in increasing T lymphocyte number and responses. Clinical studies with IRX-2 showed increases of T lymphocytes in lymphocytopenic cancer patients but relatively little effect on irradiated, lymphocytopenic patients. The present phase 1 and 2 study shows that Talpha1 enhances the effect of IRX-2 in these lymphocytopenic patients. Patients (seven) were treated with subcutaneously injected IRX-2 (200 units IL-2 equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Moreover, IL-15, IL-2, IFN-α, and IL-21 (22) have been demonstrated to promote NK- and CD8 + T cell-mediated cytotoxicity, to sustain function, and to increase antitumor immunity. Animal studies have shown that Tα1 had no effect on T cell numbers (both CD4 + and CD8 + ), and therefore, had no effect on T lymphocyte proliferation (23). Therefore, our in vitro data are consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL-15, IL-2, IFN-α, and IL-21 (22) have been demonstrated to promote NK- and CD8 + T cell-mediated cytotoxicity, to sustain function, and to increase antitumor immunity. Animal studies have shown that Tα1 had no effect on T cell numbers (both CD4 + and CD8 + ), and therefore, had no effect on T lymphocyte proliferation (23). Therefore, our in vitro data are consistent with this finding.…”
Section: Discussionmentioning
confidence: 99%
“…The delivery of IRX-2 to tumor-draining lymph nodes (LN) of HNC patients reduced pain and dysphagia, decreased tumor size and, in some patients, prolonged disease-free and overall survival [1, 2]. IRX-2 also increased the number of circulating naive and memory T cells [3], enriched T cells in tumor-draining LN [4], and promoted lymphocyte infiltrations into the tumors [5]. In addition, in vitro studies showed that IRX-2 enhanced dendritic cell (DC) maturation [6] and protected cytotoxic T lymphocytes from tumor-induced apoptosis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hadden et al [25] have reported promising histological outcomes in SCCHN patients immunized with IRX-2, a natural cytokine mixture of IL-1, IL-2, IL-6, IL-8, IL-10, IL-12, tumor necrosis factor-, granulocyte colony-stimulating factor, GM-CSF, and IFN-from activated peripheral blood mononuclear cells. Compared with controls, patients with advanced SCCHN who received a 21-day course of this immunostimulant showed evidence of dendritic cell maturation, a qualitative difference in lymph node architecture and size, as well as increased intranodal T/B cell infiltration.…”
Section: Cytokine-based Immunotherapymentioning
confidence: 89%
“…Compared with controls, patients with advanced SCCHN who received a 21-day course of this immunostimulant showed evidence of dendritic cell maturation, a qualitative difference in lymph node architecture and size, as well as increased intranodal T/B cell infiltration. They also showed significant increases in numbers of tumor-infiltrating lymphocytes [25]. A phase 3 trial is being planned.…”
Section: Cytokine-based Immunotherapymentioning
confidence: 99%